2021
DOI: 10.1021/acsami.0c20381
|View full text |Cite
|
Sign up to set email alerts
|

Lead-Free BiFeO3-BaTiO3 Ceramics with High Curie Temperature: Fine Compositional Tuning across the Phase Boundary for High Piezoelectric Charge and Strain Coefficients

Abstract: BiFeO3-BaTiO3 is a promising high-temperature piezoelectric ceramic that possesses both good electromechanical properties and a Curie temperature (T C). Here, the piezoelectric charge constants (d 33) and strain coefficients (d*33) of (1 – x)­BiFeO3-xBaTiO3 (BF-xBT; 0.20 ≤ x ≤ 0.50) lead-free piezoelectrics were investigated at room temperature. The results showed a maximum d 33 of 225 pC/N in the BF-0.30BT ceramic and a maximum d*33 of 405 pm/V in the BF-0.35BT ceramic, with T Cs of 503 and 415 °C, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(78 citation statements)
references
References 70 publications
3
67
0
Order By: Relevance
“…In previous studies, electrical properties including piezoelectricity, ferroelectricity, and electrostrain response have been widely regulated by changing the BT content, and some excellent results can be achieved 8,11–14 . For BF‐BT system with low BT content, large‐scale stripe ferroelectric domains and high Curie temperature are usually formed (Figure 1A), leading to a saturated hysteresis loop ( P–E ) and butterfly strain‐electric field curve ( S–E ) 15 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In previous studies, electrical properties including piezoelectricity, ferroelectricity, and electrostrain response have been widely regulated by changing the BT content, and some excellent results can be achieved 8,11–14 . For BF‐BT system with low BT content, large‐scale stripe ferroelectric domains and high Curie temperature are usually formed (Figure 1A), leading to a saturated hysteresis loop ( P–E ) and butterfly strain‐electric field curve ( S–E ) 15 .…”
Section: Introductionmentioning
confidence: 98%
“…[8][9][10] In previous studies, electrical properties including piezoelectricity, ferroelectricity, and electrostrain response have been widely regulated by changing the BT content, and some excellent results can be achieved. 8,[11][12][13][14] For BF-BT system with low BT content, large-scale stripe F I G U R E 1 Research motivation of this work: (A) the ε-T curves BF-BT-oxides material system with low BT content (dotted black-gray line), high BT content (strengthened relaxor state), and oxides doping (weakened relaxor state); inset of (A) is the strip domain in ceramics with low BT content. (B) Increasing BT content to form grain-dependent nanodomain, which can improve electrostrain while deteriorate ferroelectricity; (C) selective oxides doping to form grain independent-nanodomain, which can improve both electrostrain and ferroelectricity.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum piezoelectricity was exhibited at the phase boundary where rhombohedral and cubic phases are coexisted with the presence of predominant nanosized domain structures. [93]. A stripe-type macro-sized domain structure with rhombohedral symmetry was shown in 0.80BF-0.20BT.…”
Section: Ferroelectric Domain Structurementioning
confidence: 92%
“…The domain structure change in size, macro-sized domain to nano-sized domain in a polar nano region in the BF-BT system in phase across rhombohedral to pseudo-cubic was reaffirmed by piezoresponse force microscopy (PFM), which is a useful technique for determining the domain structure. Xun et al assessed the domain structure in BF-BT system, as shown in Figure 11 [93]. A stripe-type macro-sized domain structure with rhombohedral symmetry was shown in 0.80BF-0.20BT.…”
Section: Ferroelectric Domain Structurementioning
confidence: 99%
“…[4][5][6][7] Currently, the piezoelectric constant (d 33 ) values of most lead-free BF-based ceramics are ∼100-200 pC N −1 , their corresponding Curie temperature (T c ) values are ∼400-550 °C, and their piezoelectric responses and Curie temperature are usually opposites. [8][9][10][11][12] In 2004, Saito et al reported [00l]-oriented KNN-based ceramics with a high d 33 value of 416 pC N −1 and a Logering factor of f = 91%, which opened a new gate to prepare piezoelectric ceramics with good performances. 13 Subsequently, KNN-, PMN-PT-, BT-and BNT-based textured ceramics obtained great achievements in a short period of years.…”
Section: Introductionmentioning
confidence: 99%